Islamic Guidance And Counseling Through Assistance Techniques In Student Learning Activities In The New Normal Period - Amalia Nasution, Cindy Rizky (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This research is entitled assisting techniques in student learning activities during the new normal period at SMK Siti Banun Sigambal Rantauprapat. This research was conducted to determine the conditions, processes and results of student learning activities through mentoring techniques during the new normal period at SMK Siti Banun Sigambal Rantauprapat. The type of research used by researchers is qualitative research. The method used in this study uses descriptive research. With data collection techniques using observation, interviews and documentation. The results of the study revealed that the condition of student learning activities during this new normal had returned to what it was before the pandemic. It's just that there is special assistance provided by the counseling teacher in the process of student learning activities. Assistance is carried out because many students experience learning difficulties due to the large number of lessons left behind during the Covid pandemic outbreak which disrupted the process of their learning activities during this new normal. As for the assistance techniques that are carried out such as holding group guidance, group counseling, and home visits.